Analysis of the Needs of Interactive E-Lkpd on Kinematics Material Based on Dual Space Inquiry to Stimulate Students' Critical Thinking Skills - Yelli Pradila; Fuja Novitra; Akmam Akmam; Renol Afrizon (Department of Physics Universitas Negeri Padang, 2026)
This study aimed to analyze the need for developing a Dual Space Inquiry (DSI)-based interactive Electronic Student Worksheets (E-SWS) on kinematics to stimulate students’ critical thinking skills. The study was conducted at the define stage of the 4D development model, including front-end analysis, learner analysis, task analysis, concept analysis, and learning objective formulation. Data were collected through observations, interviews, questionnaires, document analysis, and critical thinking tests involving one physics teacher and 30 Grade XI students at SMA Negeri 1 Tigo Nagari. The results showed that students’ critical thinking skills were very low across all indicators. In addition, learning remained teacher-centered, student involvement in inquiry activities was limited, and the use of digital teaching materials was not yet optimal. These findings indicate the need for a DSI-based interactive E-SWS that supports inquiry-based and technology-integrated learning to stimulate students’ critical thinking skills in kinematics